2013
DOI: 10.1111/cen.12056
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of D410E, a novel mutation in the loop 3 domain of CASR, in autosomal dominant hypocalcemia and a therapeutic approach using a novel calcilytic, AXT914

Abstract: Over 60 activating mutations in the CASR gene have been identified to cause ADH so far. Here, we add one more activating mutation that causes ADH. The novel activating mutation (D410E) occurred in the loop 3 region of CASR, where its function was believed to be of little importance; therefore, this mutation may be of interest. Further clinical study will be needed to validate the effectiveness of calcilytics in treatment of ADH in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Calcilytics may indeed be employed in conditions characterized by hypocalcemia and inappropriately low PTH levels, such as ADH, caused by activating mutation of the CaSR, since they revert the abnormal set point for systemic calcium homeostasis [103,104]. In this setting, CaSR antagonists mainly act through preserving calcium eliciting paracellular calcium transport through the thick Fig.…”
Section: Calcilytics: Effects On Bonementioning
confidence: 99%
“…Calcilytics may indeed be employed in conditions characterized by hypocalcemia and inappropriately low PTH levels, such as ADH, caused by activating mutation of the CaSR, since they revert the abnormal set point for systemic calcium homeostasis [103,104]. In this setting, CaSR antagonists mainly act through preserving calcium eliciting paracellular calcium transport through the thick Fig.…”
Section: Calcilytics: Effects On Bonementioning
confidence: 99%
“…Calcimimetics are right now used to treat primary or secondary hyperparathyroidism conditions and to rescue loss-of function CaSR mutants. Conversely, calcilytics were initially meant (but till now not clinically used) to treat osteoporosis and may mitigate the effects of gain-of-function CaSR mutants [ 66 - 73 ]. Finally, it is worth recalling that the CaSR exhibits several distinct conformational states, each of which is induced and stabilized by a different ligand, allosteric agonists and antagonists included, and is linked to a particular set of intracellular signaling pathways—a property defined “ ligand-biased signaling ” [ 74 ] .…”
Section: Structure Signaling Agonists and Antagonists Of The Casrmentioning
confidence: 99%
“…8 in Table 4), which we reported as a novel mutation in the previous study (13). Another mutation of the CASR gene (c.662C>T [P221L]) was detected in one family (patient No.…”
Section: Resultsmentioning
confidence: 67%
“…IH is a heterogeneous group of disorders with various genetic mutations; mainly PTH and CASR genes affecting PTH secretion, and GCMB genes related to parathyroid embryogenesis (15). In our series, IH results from three different mutations which have been described in the literature (P221L in the CASR gene) (14), including two by our group (C106R in the GCMB gene and D410E in the CASR gene) (11, 13). We showed that IH patients possessed several SNPs in the PTH , CASR , or GCMB genes regardless of accompanying functional mutations.…”
Section: Discussionmentioning
confidence: 80%